Secondary ensnarement: Surveillance systems in the service of punitive immigration enforcement - Muñiz, Ana (Punishment & society, 2020)
Relatively little scholarly work explores US interior immigration enforcement through a surveillance lens. This article asks how US immigration authorities have designed and deployed surveillance systems to facilitate enforcement practices, specifically regarding the construction of immigrant subjects and interior apprehension and deportation. Drawing upon a qualitative analysis of 291 Department of Homeland Security documents authored between 1995 and 2017, this paper examines the evolution of a primary immigration enforcement information system currently called the Enforcement Integrated Database. The analysis reveals that over the course of 33 years, the US Government has transformed Enforcement Integrated Database from a case management system into a mass surveillance system. Specifically, I argue that immigration authorities have deployed secondary information collection in the Enforcement Integrated Database to expand (1) the volume of people under surveillance, called ensnarement targets and (2) the opportunities to categorize people as criminal or dangerous, called ensnarement opportunities. As a result, Department of Homeland Security amplifies punitive enforcement against broader populations of noncitizens and potentially, citizens as well.